Politinė filosofija kaip pašaukimas. - Bielskis, Andrius (Problems / Problemos, 2023)
The article discusses a lecture on political philosophy as a vocation, drawing on the works of Max Weber and Aristotle. It explores the academic discipline of political philosophy, contrasting Weber's views on science and ethics with Aristotle's understanding of wealth and value. The text delves into the intersection of political philosophy with ethics, economics, and societal structures, emphasizing the importance of critically evaluating political ideals and economic systems. The author reflects on the role of political philosophy in assessing societal values, wealth distribution, and the potential for meaningful human existence in the context of capitalism and technological progress.